The Influence of Polyendocrine Metabolic Ovarian Syndrome on Training Adaptations and Athletic Performance - Pirga, Gabriela; Chwajta, Gabriela; Kaczor, Gabriela; Cichocka, Weronika; Cepielik, Barbara; Antos, Martyna; chmielnicki, Filip; Paczosa, Kacper; Ostolski, Maciej; Jędruszko, Klaudia (Quality in Sport, 2026)
Background: Polyendocrine Metabolic Ovarian Syndrome (PMOS), previously known as Polycystic Ovary Syndrome (PCOS), is one of the most common endocrine disorders affecting women of reproductive age. While regular physical activity is widely recognized as a cornerstone of PMOS management, increasing evidence suggests that the syndrome itself may influence training adaptations and athletic performance. The characteristic hormonal profile of PMOS, particularly hyperandrogenism, may confer physiological advantages relevant to athletic performance. Increased androgen concentrations have been linked to greater muscle mass, enhanced strength and power production, improved oxygen transport capacity, and favorable adaptations to training, which may contribute to superior athletic performance in some women with PMOS. Aim: The aim of this narrative review was to summarise and critically discuss the current evidence regarding the relationship between PMOS, training adaptations, and athletic performance. Material and methods: A narrative review summarising and discussing evidence from observational studies (including case-control and cohort studies), systematic reviews, and meta-analyses published between 2015 and 2026, was conducted. The critical analysis focused on the physiological effects of hyperandrogenism in PMOS, training adaptations, athletic performance, and healthrelated factors influencing exercise capacity in women with PMOS. Conclusions: PMOS appears to have both beneficial and detrimental effects on exercise performance. While hyperandrogenism may confer certain physiological advantages, metabolic and psychological challenges associated with the syndrome may limit athletic potential. Further longitudinal and mechanistic studies are required to better understand the influence of PMOS on training responses and to develop individualized exercise recommendations for affected athletes.